POTRET PENDIDIKAN ISLAM PADA MASA DINASTI SYAFAWI - Mujiburrahman, Mujiburrahman (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
The Safavid Dynasty was one of the great empires that played a significant role in the history of Islamic civilization. This paper discusses the Islamic education system implemented during the Safavid period, focusing on the development of knowledge, the rise of Shia education, and the role of women in education. The education system employed three main approaches: indoctrinative education to reinforce Shia teachings, aesthetic education that supported the development of arts and industry, and military and governmental management education. The Safavid Dynasty also produced renowned scholars such as Mulla Sadra and Mir Damad, who contributed to the fields of philosophy and theology. This study uses a literature review method with content analysis from various historical sources and related literature. The findings aim to provide a deeper understanding of the Safavid Dynasty's contributions to Islamic education. The educational system during this period was based on Shia Islam, with key centers in Qom, Isfahan, and Najaf. Various madrasas were established to disseminate teachings of Islam, literature, and other Islamic sciences. In the context of Islamic education in Indonesia today, it is essential to emphasize comprehensive understanding, skill enhancement, character development, and the implementation of modern educational methods. By applying the core values from the golden period of Islamic civilization, Islamic education in Indonesia can be enriched to produce intelligent, moral, and internationally competitive generations